ECONOMIC RELATIONS BETWEEN SHAMKHALS AND ZASULAK RULERS AND THE RUSSIAN ADMINISTRATION IN THE CAUCASUS IN THE SECOND HALF OF THE 18TH CENTURY - Abdusalamov, Magomed-Pasa Balasovic (History, Archeology and Ethnography of the Caucasus, 2025)
This study reconstructs the trade relations between the Kumyk territories and the Russian Empire during the second half of the eighteenth century, utilizing archival materials from the Central State Archives of the Republic of Dagestan, specifically Collection No. 379, “Kizlyar Commandant.” The exploration of trade and economic interactions between the Russian Empire and the peoples of the North Caucasus remains a central focus within Russian Caucasus studies. Although existing scholarship has primarily addressed Russian trade and economic relations with the region in broad terms, detailed analyses of interactions with specific ethnic groups, such as the Kumyks, remain limited. This article seeks to address this scholarly gap. Employing both historical and logical research methodologies, the study ensures an objective and rigorous examination of Russian-Kumyk trade relations in their historical development. The historical method facilitates a reliable reconstruction of these relations, while the logical method enables the formulation of conclusions and generalizations. The analysis reveals that, by the second half of the eighteenth century, Russian-Kumyk trade relations had evolved to a qualitatively new stage, laying the groundwork for the Kumyk territories’ incorporation into the Russian Empire. The study concludes that: first, the integration of Kumyk polities into the Russian Empire was significantly driven by robust Russian-Kumyk trade ties and the alignment of their economic interests; second, the incorporation of the Kumyk territories into the Russian economic sphere substantially enhanced the region’s economic vitality, elevating it to a new developmental level; and third, through strategic and pragmatic economic engagement with the Kumyk polities, Russia not only solidified its economic influence in the region but also initiated political penetration, ultimately leading to Dagestan’s complete integration into the Russian Empire. Close trade connections between the Kumyk polities and Russia played a pivotal role in fostering the irreversible trend toward integration into Russia’s economic, political, and cultural spheres.